KIT mutations correlate with adverse survival in children with core-binding factor acute myeloid leukemia. Issue 4 (3rd April 2018) - Chen, Xi; Dou, Hu; Wang, Xingjuan; Huang, Yi; Lu, Ling; Bin, Junqing; Su, Yongchun; Zou, Lin; Yu, Jie; Bao, Liming
Abstract: The prevalence and clinical relevance of KIT mutations in childhood core-binding factor (CBF) acute myeloid leukemia (AML) have not been well characterized. In this study, a total of 212 children with de novo AML were enrolled from a Chinese population and 50 (23.5%) of the patients were deemed CBF-AML. KIT mutations were identified in 30% of the CBF-AML cohort. The KIT mutations were clustered in exon 17 and exon 8, and KIT mutations in exons 8 and 17 were correlated with a shorter overall survival (OS) (5-year OS: 30.0 ± 14.5% vs. 73.0 ± 8.5%, p  = .007) and event-free survival (EFS) (5-year EFS: 30.0 ± 14.5% vs. 73.0 ± 8.5%, p  = .003). Multivariate analysis revealed KIT mutations as an independent risk factor in CBF-AML. Our results suggest that KIT mutations are a molecular marker for an inferior prognosis in pediatric CBF-AML.